2000
DOI: 10.1007/s002280000218
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo indices of CYP2D6 activity: comparison of dextromethorphan metabolic ratios in 4-h urine and 3-h plasma

Abstract: In healthy Caucasian subjects, the MRs of DM to DEX in plasma obtained at 3 h correlated reasonably well with those in urine collected over the time interval 0-4 h after the dose. Nevertheless, repeatability of this plasma index should be determined before its wide use can be recommended. Finally, the interindividual variation in DEX metabolism to HM (catalyzed by CYP3A) contributes only minimally to the interindividual variability of the MRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 0 publications
4
35
0
Order By: Relevance
“…Chladek et al (2000) have confirmed that the use of dextromethorphan:dextrorphan metabolic ratio could be practiced without regard to the matrix of collection. In a study involving 95 subjects, the authors demonstrated that the phenotypes predicted from the urine collected over a 0 -4 h time interval following drug ingestion appeared to be reasonably well correlated with the phenotypes predicted from a single point determination from plasma at 3 h post dosing (Cladek et al, 2000).…”
Section: Options For Phenotyping-urine Vs Plasmasupporting
confidence: 69%
“…Chladek et al (2000) have confirmed that the use of dextromethorphan:dextrorphan metabolic ratio could be practiced without regard to the matrix of collection. In a study involving 95 subjects, the authors demonstrated that the phenotypes predicted from the urine collected over a 0 -4 h time interval following drug ingestion appeared to be reasonably well correlated with the phenotypes predicted from a single point determination from plasma at 3 h post dosing (Cladek et al, 2000).…”
Section: Options For Phenotyping-urine Vs Plasmasupporting
confidence: 69%
“…In contrast, the analysis of EM healthy subjects data from Kohler et al (1997) showed a very low correlation between the UMR in 8-h urine collection and in serum 1 h after DTM administration (r ϭ 0.19). Chladek et al (2000) found good correlation between UMR and 3-h plasma ratio (r ϭ 0.88), and Capon et al (1996) observed a similar correlation between the UMR and partial clearance of DTM to DT (r 2 ϭ 0.82). However, these studies included poor metabolizers in the analysis, and the correlations among EMs alone would be significantly lower.…”
Section: Discussionmentioning
confidence: 65%
“…Indeed, the dextromethorphan to dextrorphan urinary metabolic ratio (UMR) is routinely applied to segregate populations into two major phenotypic groups: extensive and poor metabolizers (Hou et al, 1996;Sachse et al, 1997;Tateishi et al, 1999). Although noninvasive and easy to perform, the utility of the urinary metabolic ratio to assess moderate alterations in CYP2D6 activity has not been established (Kohler et al, 1997;Tenneze et al, 1999;Chladek et al, 2000;Yeh et al, 2003).…”
mentioning
confidence: 99%
“…Hu et al [122] have shown that the plasma sample at 2, 3, 4 or 5 h or the saliva sample at 6 h could be used for determining the DMR. In one study in healthy Caucasian subjects, the DMR from urine collected over the time interval 0-4 h after the dose correlated reasonably well with those determined from plasma concentrations obtained at 3 h [123]. More recently, it has been shown that the DMRs determined using 0-8 h urine collection or a serum sample at 3 h postdose also correlate well with each other [124].…”
Section: Phenotyping Protocolsmentioning
confidence: 74%